10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Heterotaxy (HTX) is a rare condition characterized by complex congenital heart defects and a wide spectrum of extracardiac abnormalities that significantly impact survival. While molecular diagnosis is essential for clinical management, next-generation sequencing (NGS) currently identifies disease-causing variants in only 20%-30% of HTX cases. To address this diagnostic gap, we collected cases of HTX investigated by trio-based whole-exome (WES) and whole-genome sequencing (WGS) and performed detailed clinical and molecular characterization in seven children and fetuses from France and Vietnam. In parallel, we conducted a systematic review of 108 published cases to refine genotype-phenotype correlations. We identified seven variants in four key genes: DNAH9, PKD1L1, MMP21, and GDF1. The findings revealed significant phenotypic heterogeneity while highlighting strong genotype-phenotype correlations, such as the association of MMP21 and GDF1 variants with severe conotruncal malformations. Two unreported variants were identified, further expanding the mutational spectrum of laterality defects. By integrating fetopathological data with advanced genomic analyses, we further delineate the phenotypic spectrum of these conditions. Ultimately, this work underscores the high diagnostic value of NGS in prenatal and neonatal cardiology, enabling earlier diagnosis and more personalized clinical management.